(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article analyzes the ecological situation in the southern regions of Uzbekistan. Aspects that have a negative impact on ecological stability and their causes are analyzed. It also talks about the factors that serve to stabilize the ecological situation.